Analisis Penerapan SAK-ETAP (Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas Publik) pada Penyajian Laporan Keuangan Koperasi Pegawai Republik Indonesia (KPRI) “Manfaat” LPMP Jawa Tengah - Mudjiyono, Mudjiyono (Jurnal Bingkai Ekonomi (JBE), 2020)
This study aims to find and test the rules of the Entity without Public Accountability (SAK-ETAP) Financial Accounting Standards set by the Indonesian Institute of Accountants (IAI) and which is enacted in the regulation of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia No. 12/per/M.KUKM/IX/2015 concerning Cooperative Accounting Guidelines that are applied factually to KPRI "Manfaat" of Central Java LPMP. Type and Design This research is a qualitative descriptive study, namely the type of research that uses primary data in the form of financial report documents and interviews with management KPRI "Manfaat" and parties from the Cooperative and Micro, Small and Medium Enterprises of Semarang City. In order to make deeper information about the policies used in the preparation of financial statements. The results of this study, the researchers draw the conclusion that recording the financial bookkeeping of KPRI "Manfaat" of the Central Java LPMP has generally been good enough but has not applied the SAK-ETAP regulations stipulated by IAI and has not implemented legislation in accordance with the Regulation of the Minister of State for Cooperatives and Small Businesses and Menengah Republik Indonesia No.12/per/M.KUKM/IX/2015.